(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
The present experiments were conducted in the seasons 2005/06and 2006/07 at Guneid, Assalaya and New Halfa Sugar Estates in thecentral clay plain. The objectives were to investigate the response ofsugarcane (plant cane) to different doses of urea (46% N), to splitting thedose and to covering urea by a thin layer of soil. Urea doses were 150 and225 kg/feddan (one fed. = 0.42 ha). The fertilizer doses were applied eitherat 45-60 days after planting (full dose) or split into two doses: two thirds at45-60 days after planting and the other third at the age of five to six months.Covering was also compared with uncovering the fertilizer with a thin layerof soil. This factorial arrangement of treatments was laid out in arandomized complete block design in Guneid and Assalaya for Octoberplanting and in Guneid and New Halfa for June planting. The resultsrevealed that there were no significant differences in cane yield, yieldcomponents and quality of the crop of the plant cane between the rates ofurea for the October and June plantings. Splitting the dose outyielded thefull dose for June planting at New Halfa only which had a long season thatexceeded 17 months. Covering urea insignificantly outyielded theuncovered treatments. The dose 150 kg urea/fed. proved to be satisfactoryfor both cane and sugar yields for the crop of the plant cane. Therefore, adose of 150 kg urea/fed. is recommended for the plant cane crop, and asimilar study should be done for ratoon cane.